Multi-partner benchmark experiment of fatigue crack growth measurements. (August 2020) - Langlois, Raphaël; Cusset, Raphaël; Hosdez, Jérôme; Bonnand, Vincent; Blaysat, Benoit; Menut-Tournadre, Léa; Neggers, Jan; Coret, Michel; Henry, Joseph; Doquet, Véronique; Grédiac, Michel; Chiaruttini, Vincent; et al.
Highlights: Benchmark fatigue crack propagation experiments on steel and aluminium. Experiments performed by 8 teams participating to CNRS GDR 3651. Specimens geometry leading to mixed-mode and to variation of small scale yielding conditions. Curved crack paths. Comparison of stress intensity factor range and crack growth rate estimation techniques. Abstract: The design of reliable structures and the estimation of the residual fatigue life of industrial parts containing flaws or cracks rely on our ability to predict the propagation of fatigue cracks. Whereas in industrial component cracks might have a complex path due to geometry and loading, lab experiments used for identifying crack propagation law are often in pure mode I . The paper presents a synthesis of an experimental benchmark performed in the context of a French national research network. A sample has been designed to produce mixed-mode crack propagation and variation of small scale yielding conditions. Two geometries and two maximum load levels are defined for the two tested materials: a stainless steel and an aluminum alloy. Around ten participants performed experiments using their usual instrumentation. Among the eight possible parameter sets, three are selected for which detailed results are presented. A satisfying overall agreement is obtained. But, some discrepancies are evidenced due either to limitations of the instrumentation or simply because from one lab to the other the applied load is not exactly the same. It is thus concluded that one of the most important issue is boundary conditions, which is confirmed by numerical simulations.